Modified bentonite-cement-based concrete self-repairing material and preparation method thereof
By introducing microbial mineralization technology in the pussy-cement-based barrier material, the use of biomedicization to generate calcium carbonate precipitation, solve the problem of poor anti-penetration effects and erosion in existing materials in the high-salinity environment, and realize the materials of the materials, and realize the materials of the materials. Efficient repair and performance improvement.
Patent Information
- Application Number
- CN202411454670.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
AI Technical Summary
The existing bentonite-cement-based barrier materials have poor anti-seepage effect and are prone to erosion and cracking in high salinity groundwater environments, making it difficult to effectively repair cracks.
The microbial mineralization technology is used to generate calcium carbonate precipitations by adding a biomedicization to the cracks of the barbonate and the cracks of the obstruction.
The effective repair of obstruction materials in high salinity environments, enhanced the material's anti -seepage, dry fissure and corrosion resistance, and extended the service life of the material.
Smart Images

Figure BDA0005090117480000051 
Figure HDA0005090117490000011 
Figure HDA0005090117490000012
Abstract
Description
Technical Field
[0001] The invention relates to a modified bentonite-cement-based concrete self-repairing material and a preparation method thereof, and belongs to the field of concrete materials. Background Art
[0002] Solid waste landfill treatment is a common solid waste treatment technology at home and abroad. During the natural degradation of landfilled solid waste, a large amount of wastewater containing organic matter will be generated. In order to prevent groundwater pollution, solid waste landfills usually need to build vertical barrier walls around the landfill or downstream of the adjacent groundwater. Bentonite-cement is a commonly used barrier material in China, but this barrier material has problems such as poor anti-seepage effect and easy erosion and cracking in high-salinity groundwater environments.
[0003] Microbial mineralization technology is a new technology proposed in soil reinforcement research in recent years. It has the advantages of environmental protection and sustainable development. It has been developed for more than ten years. Due to its environmental protection, economy, high efficiency and controllability, it has attracted widespread attention from scholars at home and abroad, and has been applied to engineering fields such as foundation reinforcement, slope waterproofing, crack repair and contaminated soil treatment.
[0004] Microbial mineralization is a common phenomenon in nature. The mineralization mainly produces calcium carbonate precipitation, which is often used to fill or cement the pores between rocks and soils, making the rocks and soils more compact. A large number of scholars have conducted research on this and found that the main ways of calcium carbonate precipitation are urea hydrolysis, denitrification, sulfate reduction and ferric iron reduction.
[0005] In recent years, microbial induced calcium carbonate precipitation (MICP) has been gradually applied to the field of concrete crack repair, aiming to achieve concrete crack repair using biomineralization. Compared with traditional concrete crack repair methods, microbial mineralization produces fewer harmful byproducts, which provides less pollution and green repair for the environment. In addition, microorganisms can be embedded in concrete materials. When the concrete cracks, the microorganisms can be "activated" under external stimuli, thereby achieving intelligent and targeted crack self-healing repair.
[0006] CN108455934A discloses an anaerobic self-healing crack concrete, which is mainly composed of silicate cement, aggregate, mineral powder, modified cellulose fiber, anaerobic bacteria complex and water. The concrete can achieve good and long-term repair function for wider cracks, and the prepared concrete has very good strength and density.
[0007] CN110105007A discloses a three-dimensional self-repairing concrete with crack depth and width based on microorganisms. The four-element repair system consisting of microbial self-repairing agent, oxygen slow-release agent, bacteria-loaded expanded perlite, and nutrient-loaded expanded perlite is combined with polypropylene fiber to form a three-dimensional self-repairing concrete with crack depth and width. The self-repairing concrete can make up for the shortcomings of the current concrete crack self-repairing technology in the crack depth direction. While improving the durability of concrete, the concrete also has the functions of being green, lightweight, and heat-insulating.
[0008] CN114163198A discloses a high-strength and impermeable foam concrete. It includes cement, fly ash, fiber mixture and other components; the preparation method of ceramsite: mix fly ash, bentonite and red mud, add water, foam stabilizer and pore-forming agent, stir evenly, make spherical samples, dry, calcine, cool and make green bodies; mix coal gangue powder, binder and water, add to the green bodies, mix evenly, dry and make intermediates; mix thermoreversible glue with water to form a coating liquid, mix evenly with the intermediate, dry and make ceramsite. High-strength and impermeable foam concrete has the advantages of high compressive strength, good impermeability, low thermal conductivity, good thermal insulation performance, and the ability to self-repair cracks. Summary of the invention
[0009] The present invention draws on the existing technology and transfers the microbial mineralization technology to the repair of cracks in barrier materials to prepare modified bentonite-cement-based barrier materials. By studying and analyzing the sulfate corrosion resistance, anti-seepage performance and adsorption performance of ammonia nitrogen, a characteristic pollutant in groundwater of different barrier materials, the composition and preparation method of the barrier material are optimized to obtain a self-healing material that can repair cracks in the barrier material through microbial mineralization.
[0010] The invention discloses a modified bentonite-cement-based concrete self-repairing material, comprising the following components in parts by weight: 20-30 parts of modified bentonite, 15-30 parts of cement, and 50-80 parts of water, wherein the mass ratio of the modified bentonite to the cement is 0.8-1:1, and the water-solid mass ratio is 0.5-2:1.
[0011] The preparation method of the modified bentonite comprises the following steps:
[0012] (1) dissolving chitosan in glacial acetic acid solution, then slowly adding distilled water and stirring thoroughly until there are no colloidal particles, to obtain a chitosan solution;
[0013] (2) adding bentonite to the chitosan solution and leaving it to stand for 1-10 hours to allow the bentonite to be fully infiltrated, and then drying, grinding, and sieving to obtain chitosan-loaded bentonite;
[0014] (3) Mixing the bacterial solution, the nutrient solution and the chitosan-loaded bentonite in a mass ratio of 1-5:1-10:50-100 to obtain modified bentonite.
[0015] In step (1), the concentration of glacial acetic acid in the chitosan solution is 1-10wt%, more preferably 3-5wt%, the concentration of chitosan is 0.1-1wt%, more preferably 0.2-0.5wt%, and the solvent used in the chitosan solution is water.
[0016] In step (2), the ratio of chitosan solution to bentonite is 100 ml: 30-50 g; the bentonite is pretreated, the pretreatment includes washing and drying, and the drying means that the moisture content of the bentonite is less than 1%, more preferably less than 0.5%; the sieve aperture is 120-270 mesh, more preferably 200 mesh.
[0017] The bacterial concentration in step (3) is OD 600 =0.50-3.00, the nutrient solution is an aqueous solution of urea and calcium chloride, and the urea concentration is 0.50-2.50 mol·L -1 , calcium chloride concentration is 0.50-2.50 mol·L -1 .
[0018] The bacterial species in the bacterial solution are a composite bacterial group of Bacillus paramycoides and Bacillus cereus, the number ratio of Bacillus paramycoides to Bacillus cereus is 0.2-5, and the urease activity reaches 6.51 mmol·min -1 As shown above, the bacteria species was used as the nucleation site for calcium carbonate precipitation. After 15-28 days, calcite was generated at the crack and deposited along the crack surface. It has a good repair effect on the cracks of the barrier material.
[0019] As one aspect of the present invention, a method for preparing a modified bentonite-cement-based concrete self-repairing material is also disclosed, the preparation method comprising the following steps: stirring and mixing modified bentonite, cement and water in proportion for 10-30 minutes, wherein the mass ratio of modified bentonite to cement is 0.8-1, and the water-to-solid mass ratio is 0.5-2:1.
[0020] As another aspect of the present invention, it relates to the application of modified bentonite-cement-based concrete self-repairing material in groundwater in a high sulfate concentration environment. The application includes adding the prepared self-repairing material to concrete slurry or directly pouring it into existing concrete cracks.
[0021] The high sulfate concentration environment refers to a groundwater sulfate concentration of 300 ppm or more, more preferably 500 ppm or more.
[0022] Preferably, the crack width of the modified bentonite-cement-based concrete self-repairing material of the present invention after being immersed in a high sulfate concentration environment for 60 days does not exceed 0.1 mm, and more preferably does not exceed 0.09 mm.
[0023] As another aspect of the present invention, it relates to a treatment process for groundwater contamination by landfill leachate, using the modified bentonite-cement-based barrier material described above.
[0024] Technical effect of the present invention: The concrete self-repairing material of the present invention includes Bacillus paramycoides and Bacillus cereus screened from a landfill, and the strains can be screened from a landfill. These two bacteria are used as nucleation sites for calcium carbonate precipitation, and are used in combination with mineralizers and chitosan to increase the speed of mineralization of the strains at the cracks, accelerate the formation of calcite and deposit it along the surface of the cracks, and have a good repair effect on cracks in barrier materials. The repair material is used in landfills to play a role in preventing seepage, resisting cracking, and resisting erosion, and effectively controlling pollutants. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a picture of the modified bentonite-cement-based concrete self-healing material sample after solidification;
[0026] Figure 2 This is a picture of cracks in unmodified bentonite-cement-based concrete material after being corroded in a high-salt environment for 60 days at room temperature (25°C);
[0027] Figure 3 The modified bentonite-cement-based concrete self-repairing material obtained in Example 1 is used Figure 2 The picture shown is the crack condition of the unmodified bentonite-cement-based concrete material that was corroded for 60 days in a high-salt environment 28 days after repair. DETAILED DESCRIPTION
[0028] The technical solutions and applications of the present invention are described clearly and completely below through various embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0029] Example 1
[0030] Preparation of modified bentonite-cement-based concrete self-healing material: Modified bentonite, cement and water are stirred and mixed for 20 minutes in a mass ratio of modified bentonite to cement of 1:1 and a water-solid mass ratio of 0.5:1 to obtain the modified bentonite-cement-based concrete self-healing material.
[0031] The preparation method of modified bentonite includes the following steps: 1) dissolving chitosan in glacial acetic acid solution, then slowly adding distilled water and stirring until there are no colloidal particles to obtain chitosan solution; 2) adding bentonite to the chitosan solution and standing for 2 hours to allow the bentonite to be fully infiltrated, drying, grinding, and sieving to obtain bentonite loaded with chitosan; 3) mixing the bacterial solution, nutrient solution, and bentonite loaded with chitosan in a mass ratio of 1-5:1-10:50-100 to obtain modified bentonite. The concentration of glacial acetic acid in the chitosan solution described in step (1) is 5wt%, and the concentration of chitosan is 0.2wt%. The ratio of chitosan solution to bentonite described in step (2) is 100ml:50g; the bentonite is washed and dried, and the moisture content of the bentonite after drying is less than 1%; the sieve hole of the sieve is 200 mesh. The concentration of the bacterial solution in step (3) is OD 600 =2.25, the nutrient solution is an aqueous solution of urea and calcium chloride, and the urea concentration is 1.84 mol·L -1 , the concentration of calcium chloride is 2.21 mol·L -1 .
[0032] Modified bentonite-cement-based concrete self-healing materials such as Figure 1 As shown in Figure 2, at room temperature (25°C), the cracks of unmodified bentonite-cement-based concrete materials after being corroded in a high-salt environment for 60 days are as follows: Figure 2 As shown in FIG. 1 , the modified bentonite-cement-based concrete self-repairing material obtained in Example 1 was used to repair the unmodified bentonite-cement-based concrete material corroded for 60 days in a high-salt environment. The crack repair situation after 28 days is as follows: Figure 3 shown.
[0033] Comparative Example 1
[0034] No nutrient solution was added, and the rest was the same as in the embodiment.
[0035] Comparative Example 2
[0036] Urea and calcium lactate were used as nutrient solution, and the rest was the same as in the embodiment.
[0037] Comparative Example 3
[0038] No chitosan was added, and the rest was the same as in the example.
[0039] Comparative Example 4
[0040] No bacterial solution was added, and the rest was the same as in the example.
[0041] The repair materials obtained in Example 1 and Comparative Examples 1-4 were used to repair concrete cracks. After 28 days of repair, the permeability coefficient, compressive strength and erosion degree of the concrete materials were measured. The measurement results are shown in Table 1.
[0042] Table 1
[0043]
[0044] Example 2
[0045] Preparation of modified bentonite-cement-based concrete self-healing material: Modified bentonite, cement and water were stirred and mixed for 30 minutes at a mass ratio of modified bentonite to cement of 0.8:1 and a water-solid mass ratio of 2:1 to obtain the modified bentonite-cement-based concrete self-healing material.
[0046] The preparation method of modified bentonite includes the following steps: 1) dissolving chitosan in glacial acetic acid solution, then slowly adding distilled water and stirring until there are no colloidal particles to obtain chitosan solution; 2) adding bentonite to the chitosan solution and standing for 2 hours to allow the bentonite to be fully infiltrated, drying, grinding, and sieving to obtain bentonite loaded with chitosan; 3) mixing the bacterial solution, nutrient solution and bentonite loaded with chitosan in a mass ratio of 2:10:100 to obtain modified bentonite. The concentration of glacial acetic acid in the chitosan solution described in step (1) is 3wt%, and the concentration of chitosan is 0.5wt%. The ratio of chitosan solution to bentonite described in step (2) is 100ml:40g; the bentonite is washed and dried, and the moisture content of the bentonite after drying is less than 1%; the sieve hole of the sieve is 200 mesh. The concentration of the bacterial solution in step (3) is OD 600 =2.10, the nutrient solution is an aqueous solution of urea and calcium chloride, and the urea concentration is 1.90 mol·L -1 , calcium chloride concentration is 2.00 mol·L -1 .
[0047] Example 3
[0048] Preparation of modified bentonite-cement-based concrete self-healing material: Modified bentonite, cement and water were stirred and mixed for 30 minutes at a mass ratio of modified bentonite to cement of 0.9:1 and a water-solid mass ratio of 1:1 to obtain the modified bentonite-cement-based concrete self-healing material.
[0049] The preparation method of modified bentonite includes the following steps: 1) dissolving chitosan in glacial acetic acid solution, then slowly adding distilled water and stirring until there are no colloidal particles to obtain chitosan solution; 2) adding bentonite to the chitosan solution and standing for 2 hours to allow the bentonite to be fully infiltrated, drying, grinding, and sieving to obtain bentonite loaded with chitosan; 3) mixing the bacterial solution, nutrient solution and bentonite loaded with chitosan in a mass ratio of 5:10:100 to obtain modified bentonite. The concentration of glacial acetic acid in the chitosan solution described in step (1) is 5wt%, and the concentration of chitosan is 0.2wt%. The ratio of chitosan solution to bentonite described in step (2) is 100ml:30g; the bentonite is washed and dried, and the moisture content of the bentonite after drying is less than 1%; the sieve hole of the sieve is 200 mesh. The concentration of the bacterial solution in step (3) is OD 600 =2.10, the nutrient solution is an aqueous solution of urea and calcium chloride, and the urea concentration is 2.00 mol·L -1 , calcium chloride concentration is 2.10 mol·L -1 .
[0050] The present invention has been described in detail by general description and specific embodiments, but it is obvious to those skilled in the art that some modifications or improvements can be made on the basis of the present invention. Therefore, these modifications or improvements made on the basis of not departing from the spirit of the present invention all belong to the scope of protection claimed by the present invention.
Claims
1. A modified bentonite-cement-based concrete self-repairing material, comprising the following components in parts by weight: 20-30 parts of modified bentonite, 15-30 parts of cement, and 50-80 parts of water, wherein the mass ratio of modified bentonite to cement is 0.8-1:1, and the water-solid mass ratio is 0.5-2:1; The preparation method of the modified bentonite comprises the following steps: (1) dissolving chitosan in glacial acetic acid solution, then slowly adding distilled water and stirring thoroughly until there are no colloidal particles, to obtain a chitosan solution; (2) adding bentonite to the chitosan solution and leaving it to stand for 1-10 hours to allow the bentonite to be fully infiltrated, and then drying, grinding, and sieving to obtain chitosan-loaded bentonite; (3) Mixing the bacterial solution, the nutrient solution and the chitosan-loaded bentonite in a mass ratio of 1-5:1-10:50-100 to obtain modified bentonite.
2. The modified bentonite-cement-based concrete self-repairing material according to claim 1, characterized in that The concentration of glacial acetic acid in the chitosan solution in step (1) is 1-10wt%, more preferably 3-5wt%, and the concentration of chitosan is 0.1-1wt%, more preferably 0.2-0.5wt%.
3. The modified bentonite-cement-based concrete self-repairing material according to claim 1, characterized in that In step (2), the ratio of chitosan solution to bentonite is 100 ml:30-50 g; the bentonite is pretreated, the pretreatment includes washing and drying, and the drying means that the moisture content of the bentonite is less than 1%; the sieve aperture is 120-270 mesh, more preferably 200 mesh.
4. The modified bentonite-cement-based concrete self-repairing material according to claim 1, characterized in that The bacterial concentration in step (3) is OD 600 =0.50-3.00, the nutrient solution is an aqueous solution of urea and calcium chloride, and the urea concentration is 0.50-2.50 mol·L -1 , calcium chloride concentration is 0.50-2.50 mol·L -1 .
5. The modified bentonite-cement-based concrete self-repairing material according to claim 1, characterized in that The bacterial liquid is a composite bacterial group of Bacillus paramycoides and Bacillus cereus screened from landfill soil samples, and the urease activity reaches 6.51 mmol·min -1 As shown above, this strain was used as the nucleation site for calcium carbonate precipitation. After 15-28 days, calcite was generated at the cracks and deposited along the crack surface.
6. A method for preparing the modified bentonite-cement-based concrete self-repairing material according to any one of claims 1 to 5, comprising the following steps: The modified bentonite, cement and water are stirred and mixed according to the proportion for 10-30 minutes; wherein the mass ratio of the modified bentonite to cement is 0.8-1:1, and the mass ratio of water to solid is 0.5-2:
1.
7. Use of the modified bentonite-cement-based concrete self-repairing material according to claims 1-5 in groundwater in an environment with high sulfate concentration.
8. The use according to claim 7, characterized in that The prepared self-repairing material is added to the concrete slurry or directly poured into the existing concrete cracks.
9. The use according to claim 7, characterized in that The high sulfate concentration environment refers to a groundwater sulfate concentration of 300 ppm or more, more preferably 500 ppm or more.
10. The use according to claim 9, characterized in that The crack width of the self-healing material after being immersed in a high sulfate concentration environment for 60 days does not exceed 0.1 mm, and more preferably does not exceed 0.09 mm.
Citation Information
Patent Citations
Anaerobic bacteria crack self-healing concrete
CN108455934A
Microorganism-based crack depth-width three-dimensional self-repairing concrete and preparation method thereof
CN110105007A
High-strength impermeable foam concrete and preparation method thereof
CN114163198A
Cited By
Microbial crack repairing agent based on industrial solid waste and repairing method
CN120463532A
Feeding self-healing agent, preparation method thereof and application of feeding self-healing agent in self-adjusting cement-based material
CN121135215A
Tunnel crack repairing material containing modified marine sludge carrier and preparation method
CN122233726A
A tunnel crack repair material containing modified marine silt carrier and its preparation method
CN122233726B